Chukchi Sea Polar Bear Location Data 1985-1996 - U.S. Geological Survey, Alaska Science Center Polar Bear Research Program (USGS Science Data Catalog, 2015)
These data are the raw location data collected from satellite radio-collars fitted on adult female polar bears in the Chukchi Sea, between 1985-1996. The collars were worn by adult female polar bears ranging within the Chukchi Sea subpopulation boundaries as identified by the International Union for the Conservation of Nature’s Polar Bear Specialist Group. ARGOS collars were programmed to transmit for 8 hours centered on 0:00 UTC once every three days. Thus, for two consecutive days the ARGOS collar did not transmit location data.